Analysing the Role of Service Encounter Quality in Enhancing Customer Delight in Chinese Hotpot Restaurant - Agatha, Margareth Gabriel; Martheus, Felix; Guntama, Feriawan; Wibowo, Rendi; Juliana, Juliana (Universitas Bina Sarana Informatika, 2025)
This study examines the role of service encounter quality in enhancing customer delight at Chinese hotpot restaurants in Jakarta. Employing a quantitative research approach, data were collected from 100 customers of various prominent Chinese hotpot establishments through structured questionnaires. The analysis service encounter quality have a significant positive effect on customer delight. These findings underscore the necessity for restaurant managers to prioritize not only product quality but also the quality of customer interactions to foster memorable and delightful dining experiences. By highlighting the pivotal role of service encounters in experiential dining, this study adds to the existing literature on customer experience management and provides practical insights for improving customer engagement in the restaurant industry.